Incomplete Uterine Perforation After Intrauterine Device Insertion: Diagnosis and Retrieval by Flexible Hysterofibroscopy in Three Very Rare Cases - Jen-Ching Lin; Yun-O Chen (Elsevier, 2004)
Objective: Incomplete uterine perforation after intrauterine device (IUD) insertion has occasionally been observed. We report on three patients who underwent flexible hysteroscopy for localization and retrieval of these intramural devices. Case Reports: Three Taiwanese women presented with lower abdominal pain, discomfort during defecation and frequent urination. All used a Nova-T IUD for contraception. Sonography suggested dislocation of the IUD or perforation, and pelvic examination revealed missing strings. All the women underwent flexible hysteroscopy to localize and retrieve the devices. The hysteroscopic examination indicated partial perforation or embedding of the device into the cervical or uterine wall. Retrieval was smoothly performed without cervical dilatation or anesthesia in all three women. All devices were directly retrieved using the grasping forceps of the flexible hysterofibroscope. The subsequent courses were smooth and uneventful. Conclusion: Flexible hysteroscopy is a simple and useful tool for diagnosis and retrieval of intramural IUDs. The instant removal of an IUD that has incompletely perforated the uterine wall might prevent complete uterine perforation.